IL-1β promotes glutamate excitotoxicity: indications for the link between inflammatory and synaptic vesicle cycle in Ménière’s disease - Na Zhang; Yongdong Song; Hanyue Wang; Xiaofei Li; Yafeng Lyu; Jiahui Liu; Yurong Mu; Yan Wang; Yao Lu; Guorong Li; Zhaomin Fan; Haibo Wang; et al. (Cell Death Discovery)
Abstract Ménière’s disease (MD) is a complex inner ear disorder characterized by a range of symptoms, with its pathogenesis linked to immune-related mechanisms. Our previous research demonstrated that IL-1β maturation and release can trigger cell pyroptosis, exacerbating the severity of the endolymphatic hydrops in a mouse model; however, the specific mechanism through which IL-1β influences MD symptoms remains unclear. This study conducted on patients with MD examined changes in protein signatures in the vestibular end organs (VO) and endolymphatic sac (ES) using mass spectrometry. Gene ontology and protein pathway analyses showed that differentially expressed proteins in the ES are closely related to adhesion, whereas those in the VO are related to synapse processes. Additionally, the study found elevated expression of Glutaminase (GLS) in the VO of MD patients compared to controls. Further investigations revealed that IL-1β increased glutamate levels by upregulating GLS expression in HEI-OC1 cells. Treatment with a GLS inhibitor or an IL-1β receptor antagonist alleviated auditory-vestibular dysfunction and reduced glutamate levels in mice with endolymphatic hydrops. These findings collectively suggest that imbalanced neurotransmitter release and immune responses contribute to the pathology of MD, potentially explaining the hearing loss and vertigo associated with the disease and offering new avenues for therapeutic interventions.